2024
DOI: 10.1093/bfgp/elae019
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling aging dynamics in the hematopoietic system insights from single-cell technologies

Xinrong Jin,
Ruohan Zhang,
Yunqi Fu
et al.

Abstract: As the demographic structure shifts towards an aging society, strategies aimed at slowing down or reversing the aging process become increasingly essential. Aging is a major predisposing factor for many chronic diseases in humans. The hematopoietic system, comprising blood cells and their associated bone marrow microenvironment, intricately participates in hematopoiesis, coagulation, immune regulation and other physiological phenomena. The aging process triggers various alterations within the hematopoietic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 145 publications
0
1
0
Order By: Relevance
“…Another study identified a distinct expression pattern of circular RNAs (circRNAs) between frail and robust elderly individuals, highlighting their potential as biomarkers for frailty [ 32 ]. Innovations in single-cell RNA sequencing have enabled the comprehensive profiling of immune cells across various conditions, revealing an age-dependent accumulation of transcriptome heterogeneity in immune cells and identifying specific transcription factors and distinct cellular trajectories associated with aging [ 59 , 60 ]. Furthermore, a frailty-specific monocyte subset characterized by the high expression of the long noncoding RNAs NEAT1 and MALAT1 provides new insights into immune senescence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study identified a distinct expression pattern of circular RNAs (circRNAs) between frail and robust elderly individuals, highlighting their potential as biomarkers for frailty [ 32 ]. Innovations in single-cell RNA sequencing have enabled the comprehensive profiling of immune cells across various conditions, revealing an age-dependent accumulation of transcriptome heterogeneity in immune cells and identifying specific transcription factors and distinct cellular trajectories associated with aging [ 59 , 60 ]. Furthermore, a frailty-specific monocyte subset characterized by the high expression of the long noncoding RNAs NEAT1 and MALAT1 provides new insights into immune senescence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%